Examination of CA1 Hippocampal DNA Methylation as a Mechanism for Closing of Estrogen’s Critical Window - Sinha, Puja; Rani, Asha; Kumar, Ashok; Riva, Alberto; Brant, Jason Orr; Foster, Thomas C. (Frontiers in Aging Neuroscience, 2021)
There is a critical window for estrogen replacement therapy, beyond which estradiol (E2) fails to enhance cognition and N-methyl-D-aspartate (NMDA) receptor function, and E2-responsive transcription decreases. Much less attention has been given to the mechanism for closing of the critical window, which is thought to involve the decline in estrogen signaling cascades, possibly involving epigenetic mechanisms, including DNA methylation. This study investigated changes in DNA methylation in region CA1 of the hippocampus of ovariectomized female rats over the course of brain aging and in response to E2-treatment, using whole genome bisulfite sequencing. Differential methylation of CpG and non-CpG (CHG and CHH) sites and associated genes were characterized in aged controls (AC), middle-age controls (MC), and young controls (YC) and differential methylation in response to E2-treatment (T) was examined in each age group (AT-AC, MT-MC, YT-YC). Possible candidate genes for the closing of the critical window were defined as those that were hypomethylated by E2-treatment in younger animals, but were unresponsive in aged animals. Gene ontology categories for possible critical window genes were linked to response to hormones (Adcyap1, Agtr2, Apob, Ahr, Andpro, Calm2, Cyp4a2, Htr1b, Nr3c2, Pitx2, Pth, Pdk4, Slc2a2, Tnc, Wnt5a), including G-protein receptor signaling (Gpr22, Rgs4). Other possible critical window genes were linked to glutamate synapses (Nedd4, Grm1, Grm7, Grin3a). These results suggest that decreased E2 signaling with advanced age, and/or prolonged E2 deprivation, results in methylation of E2-responsive genes, including those involved in rapid E2 signaling, which may limit subsequent transcription.